Hyperexcitable PV interneurons render hippocampal microcircuitry vulnerable to amyloid beta: Development of new models and analysis methods/amyloid/Abeta. (7th December 2020) - Hijazi, Sara; Heistek, Tim; Mansvelder, Huibert D.; Smit, August B.; van Kesteren, Ronald E.
Abstract: Background: Hippocampal Parvalbumin (PV) neurons are GABAergic inhibitory interneurons that provide feedback and feedforward inhibition. They control hippocampal local circuitry and are essential for spatial learning and memory. Accordingly, their dysfunction has been associated with Alzheimer's disease (AD). Previously, we showed that an early amyloid‐beta dependent PV hyperexcitability is causally involved in hippocampal circuit dysfunction and cognitive impairment in a mouse model of AD. Here, we investigate the short‐ and long‐term effects of PV hyperexcitability on hippocampal function and test whether PV neuron hyperexcitability can render hippocampal circuits vulnerable to amyloid beta. Method: We use chemogenetics (hM3Dq‐activating receptor with clozapine‐N‐oxide) in order to increase PV neuron activity for three weeks. We then train the mice in the Morris water maze (MWM) in order to asses hippocampus‐dependent spatial memory. Finally, using whole‐cell patch‐clamp recordings, we investigate PV and pyramidal neuron excitability and synaptic transmission in the hippocampus. Result: We found that prolonged activation of PV neurons disrupts synaptic transmission and causes spatial memory deficits on the short‐term, while on the long‐term, natural compensatory mechanisms restore synaptic transmission and spatial memory. A single low‐dose of amyloid‐beta disrupts long‐term restoration of hippocampal synaptic transmission when PV neurons are hyperexcitable. Specifically, under these conditions, amyloid‐beta impairs PV neuron function, resulting in significant spatial memory deficits. Conclusion: Taken together, our data show that an induced hyperexcitablity state of PV neurons render hippocampal circuitry vulnerable to amyloid‐beta.